Problem Based Learning: Mengembangkan Keterampilan Peserta Didik dalam Menemukan Peluang Hubungan Antar Variabel Materi Sistem Reproduksi di MTs Negeri 8 Gunungkidul - Kendah Romi Widiyastuti (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Learning resources other than teachers who play an important role in helping the learning process to achieve Competency Standards (SK) and Basic Competencies (KD) are teaching materials. Learning using PBL (Problem Based Learning) based teaching materials encourages students to think about solving the problems presented. This allows students to think critically by paying attention to the problems at hand. This study aims to determine the application of PBL-based teaching materials to human reproductive system learning to the ability to find opportunities for MTs students. The subject of the study was students of IX MTs Negeri 8 Gunungkidul for the 2022/2023 academic year. Data was collected through observation, interviews, and interviews. The results of the study found that the application of PBL-based teaching materials can develop students' ability to find opportunities for relationships between variables in the reproductive system material. PBL-based teaching materials can be developed to be even better by teachers to improve students' thinking skills.